Pineapple grenade : a novel - Dorsey, Tim (Dorsey, Tim. Serge Storms series., 2012)
Serge Storms has finagled his way into becoming a secret agent in Miami, spying for the president of a banana republic. Will he still have time for a cocktail before Homeland Security brings him down?